Seasonal Dynamics in the Chemistry and Structure of the Fat Bodies of Bumblebee Queens - Votavová, Alena; Tomčala, Aleš; Kofroňová, Edita; Kudzejová, Michaela; Šobotník, Jan; Jiroš, Pavel; Komzáková, Olga; Valterová, Irena (PloS one, 2015)
Insects' fat bodies are responsible for nutrient storage and for a significant part of intermediary metabolism. Thus, it can be expected that the structure and content of the fat body will adaptively change, if an insect is going through different life stages. Bumblebee queens belong to such insects as they dramatically change their physiology several times over their lives in relation to their solitary overwintering, independent colony foundation stage, and during the colony life-cycle ending in the senescent stage. Here, we report on changes in the ultrastructure and lipid composition of the peripheral fat body of Bombus terrestris queens in relation to seasonal changes in the queens' activity. Six life stages are defined and evaluated in particular: pharate, callow, before and after hibernation, egg-laying, and senescence. Transmission electron microscopy revealed that the fat body contained two main cell types-adipocytes and oenocytes. Only adipocytes reveal important changes related to the life phase, and mostly the ration between inclusion and cytoplasm volume varies among particular stages. Both electron microscopy and chemical analyses of lipids highlighted seasonal variability in the quantity of the stored lipids, which peaked prior to hibernation. Triacylglycerols appeared to be the main energy source during hibernation, while the amount of glycogen before and after hibernation remained unchanged. In addition, we observed that the representation of some fatty acids within the triacylglycerols change during the queen's life. Last but not least, we show that fat body cell membranes do not undergo substantial changes concerning phospholipid composition in relation to overwintering. This finding supports the hypothesis that the cold-adaptation strategy of bumblebee queens is more likely to be based on polyol accumulation than on the restructuring of lipid membranes.
Keywords: mastné kyseliny; Adaptation, Physiological; Seasons; Fatty Acids; hibernace; Cell Membrane; Hibernation; tukové těleso; Animals; Fat Body; roční období; Bees; fyziologická adaptace; zvířata; včely; buněčná membrána